A reduced linearization method for solving problems of nonlinear optimization - Panferov, S.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
An approach to solving a problem of optimization with constraints is proposed. An algorithm based on a synthesis of such methods as the separation of variables, the dimension reduction, and the method of reducing the original problem to an auxiliary one. A number of applicability conditions for this algorithm and a convergence theorem are formulated.